Further characterization of Shwachman-Diamond syndrome: Psychological functioning and quality of life in adult and young patients - Perobelli, Sandra; Nicolis, Elena; Assael, Baroukh Maurice; Cipolli, Marco (American journal of medical genetics. Part A, 2012)
To assess psychosocial functioning and quality of life in a representative group of adult and young patients with Shwachman–Diamond syndrome (SDS), all patients 3 years old and over included in the Italian SDS Registry were investigated using an ad‐hoc questionnaire for information about demography, education, socialization, rehabilitation therapy, and standardized questionnaires [SF‐36, Child Behavior Check‐List (CBCL)] for quality of life and behavior. Results were compared with those of a Cystic Fibrosis (CF) patient group, matched for age and sex. Eighty‐one percent of patients answered. All but one adult patient lived with their parents, 24% had independent income, and 57% had a driver's license. Different levels (from mild to severe) of cognitive impairment were reported by 76% of the adults and by 65% of the young patients. These data are significantly lower than those of the CF group. Both groups present low scores in the emotional and mental health evaluations at SF‐36, but SDS patients reported significantly more limitations in physical functioning (PF) and more body pain (BP) experiences. As reported by parents at CBCL, young SDS patients show more “social problems” (in the clinical area 31% SDS vs. 6% CF), “attention deficits disorder” (29% SDS vs. 0%CF), and “somatic complaints” (24% SDS vs. 12% CF). Psychosocial functioning is impaired in the majority of SDS patients, significantly more than in patients affected by CF. © 2012 Wiley Periodicals, Inc.